The Effectiveness of Consumer Protection Law in Overcoming Misleading Marketing in the Food and Beverage Industry - Bobby Ferly; Apriyanto Apriyanto; Rizky Wisudawan Katjong (Ipso Jure, 2024)
Evaluate the effectiveness of consumer protection law in addressing misleading marketing in the food and beverage industry, which often involves inaccurate product information. On the other hand, misleading marketing not only harms consumers economically, but can also have a serious impact on public health. Therefore, the active role of consumers in verifying product information is becoming increasingly important amidst the rise of misleading claims in the food and beverage sector. This research uses a normative juridical method with a statutory and conceptual approach to analyze Law No. 8/1999 on Consumer Protection. This method allows researchers to evaluate existing regulations and understand the concept of consumer protection in the context of misleading marketing. The results show that although regulations are in place, stricter implementation and enforcement are needed to protect consumers from health risks and economic losses due to misleading product information. The research suggests increased supervision by authorities, such as BPOM, as well as better collaboration between the government, businesses, and consumers to create a fairer and more transparent trading environment in the food and beverage sector.